Salvage CyberKnife-Based Reirradiation of Patients With Recurrent Prostate Cancer: The Single-Center Experience. (6th July 2018) - Miszczyk, Leszek; Stąpór-Fudzińska, Małgorzata; Miszczyk, Marcin; Maciejewski, Bogusław; Tukiendorf, Andrzej
The aim of this study was to evaluate CyberKnife-based radioablation as a salvage treatment for prostate cancer postirradiation relapses based on a group of patients disqualified from available conventional methods of salvage treatment. Thirty-eight patients were treated with a fraction dose varying from 5.5 to 10 Gy (median 7.35) to a total dose of 18 to 36.25 Gy (median 36.25). In all, 55.3% of patients had androgen deprivation therapy during this time. Nine patients had oligometastases in the salvage time. The follow-up varied from 1.6 to 46.4 months (mean 19.7, median 14.4). In all, 92.6% to 97.4% of patients had no gastrointestinal acute adverse effects; no effects higher than G1 were noted. There were particular (up to 4.8%) G2 late gastrointestinal effects. The percentage without genitourinary acute effects varied from 59.1% to 78.9%; 3.7% had G3 toxicity. G3 late genitourinary toxicity appeared 3 times, the maximal percentage being 12.5% (24 months after salvage treatment). The nadir of prostate-specific antigen median was 0.24 ng/mL (9 months after treatment). Twelve (31.6%) patients failed in the timeline of 6 to 42 months after salvage treatment (mean 18.7, median 16.5)—5 due to dissemination. In 2 cases, progression in existing metastases was identified. Five (13.2%) patients had biochemical failure without additional metastases (local relapses); hence, local control was 86.8%. The failure risk is strongly influenced by initial disease stage and presalvage prostate-specific antigen concentration. The obtained results permit us to conclude that such a treatment could be an effective and safe option for prostate cancer postirradiation relapse salvage treatment.